1987
DOI: 10.1002/bit.260290911
|View full text |Cite
|
Sign up to set email alerts
|

Controlled expression and purification of human immune interferon from high‐cell‐density fermentations of Saccharomyces cerevisiae

Abstract: Conditions for high-cell-density fermentations of Saccharomyces cerevisiae strains producing recombinant-DNA-derived proteins were established. Strains producing human immune interferon (IFN-gamma) from the constitutive PGK promoter failed to grow to high cell densities and exhibited low plasmid stability. Regulated expression of IFN-gamma was obtained in similar strains by employing a hybrid yeast GPD promoter that was subject to carbon source regulation due to the presence of regulatory DNA sequences from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…33 ) Under the induced conditions, where the high cell densities with higher plasmid stability were maintained by switching from a glucose-limiting feed to a galactoselimiting feed, they obtained human interferon (IFN-y) production as 3 ~ 5% of total cellular proteins (2 g IFNII fermentation culture) by using a hybrid yeast G P D (glyceroaldehyde 3-phosphate dehydrogenase gene) promoter that was subject to carbon source regulation due to the presence of regulatory DNA sequences from the yeast GAL 1,10 intergenic region. Suomalainen reported that the glucose concentrations above 5% caused repression of the oxidative pathway, resulting in ethanol accumulation even under aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…33 ) Under the induced conditions, where the high cell densities with higher plasmid stability were maintained by switching from a glucose-limiting feed to a galactoselimiting feed, they obtained human interferon (IFN-y) production as 3 ~ 5% of total cellular proteins (2 g IFNII fermentation culture) by using a hybrid yeast G P D (glyceroaldehyde 3-phosphate dehydrogenase gene) promoter that was subject to carbon source regulation due to the presence of regulatory DNA sequences from the yeast GAL 1,10 intergenic region. Suomalainen reported that the glucose concentrations above 5% caused repression of the oxidative pathway, resulting in ethanol accumulation even under aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…-Glucose was replaced by glycerol for L-asparaginase, a constitutive anti-leukemia intracellular enzyme, production from E. coli by Squibb in 1969 (Robison and Berk, 1969). -A controlled, galactose-induced, high cell density, S. cerevisiae production process for 2 g/L human immune interferon, rivaling production from E. coli approved in 1986, was developed by Amgen in 1987 (Fieschko et al, 1987). -A process to produce an Aspergillus glucoamylase by expressing the enzyme in S. cerevisiae and then using the 1959-1968 1969-1978 1979-1988 1989-1998 1999-2008 Milestone Mutation/selection Biotransformations Biopesticides Rise in approvals (7/1994-15/1995-25/1996) rDNA Equipment and instrumentation…”
Section: Subject Matter and Examplesmentioning
confidence: 99%
“…Thus, the value of K should be equal to the difference between the two steadystate product concentrations obtained at 24°C and 30"C, P24 and P30, respectively. The dead time, 8, and the time constant, T~, in this transfer function must be determined from available experimental data. The second transfer function, G2(s), corresponds to the reactor response to a change in the feed concentration.…”
Section: Regulated Gene Expression In Chemostat Culturementioning
confidence: 99%
“…For gene turn-on experiments, K = AP = PZ4 -P30; for gene turn-off, K = -AP. 7 2 is equal to the inverse of dilution rate, D. The remaining two parameters, 8 and T~, must be estimated from curve-fitting of available experimental data to the equation. Figure 10 shows the dynamics of P-galactosidase concentration in two chemostat cultures after a temperature shift from 30°C to 24°C.…”
Section: Regulated Gene Expression In Chemostat Culturementioning
confidence: 99%